Integration of employee development practices and organisational performance of local government - Mohd Nazri Zakaria; Mohd Rushdan Yasoa; Mohd Safwan Ghazali; Mohd Asrul Hery Ibrahim; Mohammad Ismail (University of Malaya, 2017)
This study attempts to highlight the relationship between employee development practices and organisational performance of local government in Peninsular Malaysia. It examines the employee development practices, particularly, formal training, informal coaching and empowerment in strengthening organisational performance specifically in the public sector. Information was gathered from 420 selected departments of City Council and Municipal Council in Peninsular Malaysia. The findings of the study showed that employee development practices have significant positive impact on the performance of local government. More importantly, informal coaching extracts higher influence on performance compared to formal training and empowerment. Finally, the study provides practical implications.